First record of invasive mosquito aedes albopictus in tabasco and Yucatan, Mexico - Garza Hernandez, Javier Alfonso (2018)
The invasive mosquito Aedes albopictus is currently distributed in most of the southern Mexican region. Since the species was first recorded in the state of Tamaulipas, in northeastern Mexico in 1988, it has expanded its distribution throughout the Sierra Madre Oriental and Gulf of Mexico to the Neotropical region of the country. Currently the species occurs in the states of Tamaulipas, Coahuila, Nuevo Leon, Veracruz, Chiapas, Morelos, Quintana Roo, Sinaloa, San Luis Potosi, and Hidalgo. This is the first report of the mosquito in the states of Tabasco and Yucatan and the confirmation of its presence in Quintana Roo state. Aedes albopictus has been incriminated as a secondary vector of diseases such as those caused by dengue, chikungunya, and Zika viruses, which have caused epidemic outbreaks in most tropical and subtropical regions of Mexico; therefore, surveillance for the detection of Ae. albopictus is paramount so that targeted control strategies can be implemented for its control throughout Mexico.